Humorous Writing Exercise Using Internet Memes On English Classes - Abdul Aziz Turhan Kariko (Lingua Cultura, 2012)
This study discusses Internet memes found by Internet users and how they appeal for them, by deconstructing what internet meme is and what it does. Analysis are conducted especially on how the relation between images, text, and meanings connect with each other to form social messages, political messages, universal emotions, or merely to make humor and entertain its users. Researcher examines five samples of internet memes on the internet and decodes their relation between images, texts, and meanings using semiotics. These samples are then introduced as writing assignments to two BINUS University’s English department classes and one Global English Class. The study reveals that humor and creativity in using internet memes are related to the students’ achievement in their studies.